The Framework for Action and the Legacy of the Civil Rights Movement - Smith, Derik (The Journal of Bahá’í Studies, 2025)
Individuals, communities, and institutions throughout the world are learning about how the evolving framework for action described in the Plans of the Universal House of Justice can be used to create meaningful, lasting transformation in society. This paper suggests that insights into the efficacy of the framework can be gleaned through consideration of its relation to social transformation movements of the past. In particular, contemplation of the history of the Southern civil rights movement engenders appreciation for the prescriptions of the House of Justice. Framework concepts such as the importance of sincere love for humanity, unified action, continuity of action, process-oriented planning, and the connection between service and transformation were vital African American organizers of the civil rights movement. Ultimately, the presentation submits that we honor the richest legacy of the civil rights movement by pursuing—as best we can—noble endeavors in alignment with the framework for action laid out in the Plans of the Universal House of Justice.